Health-preserving system at Zaporozhye State Medical University - Волкова, Юлія Володимирівна; Федорченко, Руслана Анатоліївна; Волкова, Ю. В.; Федорченко, Р. А.; Volkova, Yu. V.; Fedorchenko, R. A. (Минск : БГУ, 2020)
In the article, the author reveals the main components of the health-preserving system of Zaporizhzhia State Medical University: rational organization of the educational process, taking into account all sanitary standards and hygienic requirements, organization of optimal physical activity of students, organization of rational nutrition for students, high-quality medical care, ensuring life safety, educational and pedagogical activities shaping the value of health and ways to strengthen it. Particular attention is paid to the issues of involving teachers in the process of forming motivation to lead a healthy lifestyle among students. В статье автор раскрывает основные составляющие системы здоровьесберегающей деятельности Запорожского государственного медицинского университета: рациональная организация учебного процесса с учетом всех санитарных норм и гигиенических требований, организация оптимальной физической активности студентов, организация рационального питания студентов, качественное медицинское обслуживание, обеспечение безопасности жизни, образовательная и педагогическая деятельность, формирующая ценность здоровья и пути его укрепления. Особое внимание уделяется вопросам вовлечения преподавателей в процесс формирования мотивации к ведению здорового образа жизни у студентов.
Оздоровительная система Запорожского государственного медицинского университета
Keywords: health-saving technologies; medical students; educational process; occupational safety and health; здоровьесберегающие технологии; студенты-медики; учебный процесс; охрана труда